Birefringence for Elliptical-Core Fibers with Low Ellipticities - Mohammed, Miami A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Model birefringence was measured for elliptical-core fibers with low ellipticities, note the birefringence depends strongly on the frequency, especially when fiber is being operated near the higher mode cutoff where ν for circular fiber of the single-mode type that correspond to the birefringence maximum. When ν this also correspond to the birefringence maximum that can be introduced in an elliptical core fiber while still operating in the single-mode regime near the higher mode cutoff. Also the birefringence is proportional to the fiber core ellipticity when core ellipticity is much less than unity, but this birefringence deviates from the linear for the large core ellipticities.